Comparison of Two Methods of Estimating Reader Variability in QT Interval Measurements in Thorough QT/QTc Studies. Issue 2 (13th February 2014) - Salvi, Vaibhav; Karnad, Dilip R.; Kerkar, Vaibhav; Panicker, Gopi Krishna; Natekar, Mili; Kothari, Snehal
<x xml:space="preserve">Abstract</x> Background Two methods of estimating reader variability (RV) in QT measurements between 12 readers were compared. Methods Using data from 500 electrocardiograms (ECGs) analyzed twice by 12 readers, we bootstrapped 1000 datasets each for both methods. In grouped analysis design (GAD), the same 40 ECGs were read twice by all readers. In pairwise analysis design (PAD), 40 ECGs analyzed by each reader in a clinical trial were reanalyzed by the same reader (intra‐RV) and also by another reader (inter‐RV); thus, variability between each pair of readers was estimated using different ECGs. Results Inter‐RV (mean [95% CI]) between pairs of readers by GAD and PAD was 3.9 ms (2.1–5.5 ms) and 4.1 ms (2.6–5.4 ms), respectively, using ANOVA, 0 ms (–0.0 to 0.4 ms), and 0 ms (–0.7 to 0.6 ms), respectively, by actual difference between readers and 7.7 ms (6.2–9.8 ms) and 7.7 ms (6.6–9.1 ms), respectively, by absolute difference between readers. Intra‐RV too was comparable. Conclusions RV estimates by the grouped‐ and pairwise analysis designs are comparable.